Ageism and Mistreatment of Older Workers Current Reality, Future Solutions - Brownell, Patricia; Kelly, James J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
This book promotes an understanding of ageism, discrimination and mistreatment of older adult workers, incorporating an international human rights perspective. The impact of ageism on the mistreatment of older adult workers has not to date been examined in depth through the lens of international human rights instruments, nor has discrimination against older adults in the workplace been framed as a form of elder abuse for research and policy making purposes. This book presents a multi-disciplinary exploration of these themes as they affect work and retirement of older adults. It reflects the view that older people who choose to work into old age should be able to do so in enabling work environments that promote dignity and are free of abuse. The contributing authors come from many disciplines, including law, psychology, social work, business, and international affairs. Many are members of the International Network for the Prevention of Elder Abuse (INPEA), a non-governmental organization with consultative status at the United Nations, and have devoted their professional careers to increase awareness and understanding of elder abuse in order to prevent it. The editors hope that broadening the framework within which elder abuse in the workplace is understood will stimulate further research, policy and program development to address this troubling social problem.
Foreword (Gloria M. Gutman) -- Preface (Patricia Brownell & James J. Kelly) -- Part I: Understanding Mistreatment of Older Workers: A Human Rights Perspective and Conceptual Framework -- Chapter 1: Older Workers and Human Rights: National and International Policies and Realities (Denise Gosselin Caldera) -- Chapter 2: Definitions and Conceptual Framework for Understanding Ageism and Mistreatment of Older Workers (Patricia Brownell & Mebane Powell) -- Part II: Current Reality -- Chapter 3: Harassment of Older Adults in the Workplace (Amy Blackstone) -- Chapter 4: What Do Newspapers Say About Older Adults in the Workplace? (Mebane Powell) -- Chapter 5: The Evolution of Retirement as Systematic Ageism (Lynn McDonald) -- Part III: Future Solutions -- Chapter 6: Creating Supportive Workplace Environments for Older Workers (Elizabeth Ciampa & Roslyn Chernesky) -- Chapter 7: Human Resource Departments and Older Adults in the Workplace (James Woolever) -- Chapter 8: Counseling Older Workers Confronting Ageist Stereotypes and Discrimination (Margo Jackson) -- Chapter 9: Legal and Legislative Issues in Protecting Older Adults in the Workplace: An International Perspective (Charmaine Spencer) -- Chapter 10: International Protection for the Human Rights of Older People: History and Future Prospects (Israel Doron, Bethany Brown & Susan B. Somers) -- Looking Ahead (Patricia Brownell & James J. Kelly).
Keywords: Social sciences; Geriatrics; Aging -- Research; Applied psychology; Social Sciences; Aging; Human Rights; Psychotherapy and Counseling; Human Resource Management; Geriatrics/Gerontology.